Program “SUPER” untuk Meningkatkan Komitmen Perkawinan - Alfi Fatima Yudani; Tina Afiatin (Faculty of Psychology, Universitas Gadjah Mada, 2018)
Low marital commitments can cause many marital problems. Therefore, interventions that can increase marriage commitments are needed. This study aims to determine the effect of the